1986
DOI: 10.1111/j.1432-1033.1986.tb09630.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structures of mutationally altered ribosomal protein L7/L12 and their effects on cellular growth and translational accuracy

Abstract: The amino acid sequences of mutationally altered ribosomal protein L7/L12 from four different rplL mutants of Escherichia coli were determined and correlated with some features of the mutant ribosomes. Two of the rplL mutations are deletions around position 40, which give rise to a shortened hinge region between the two domains of L7/L12. The other two mutants harbor point mutations at position 74 (Gly+Asp) or at position 82 (Glu+Lys), which are in or close to an evolutionarily conserved sequence in the C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…Studies during the 1970s first demonstrated the requirement of L7/L12 for the functions of a wide variety of essential translation factors, including G and non-G proteins, in protein synthesis in vitro (7,8,27,28). Subsequent studies isolated mutants of L7/L12, which altered the fidelity and speed of protein synthesis in vivo (29). Recent in vitro studies have converged on a small cluster of conserved, positively charged or aliphatic residues of L7/L12, which may interact with the G protein factors EF-Tu, EF-G, RF3, and IF2 (9,10,30).…”
Section: Discussionmentioning
confidence: 99%
“…Studies during the 1970s first demonstrated the requirement of L7/L12 for the functions of a wide variety of essential translation factors, including G and non-G proteins, in protein synthesis in vitro (7,8,27,28). Subsequent studies isolated mutants of L7/L12, which altered the fidelity and speed of protein synthesis in vivo (29). Recent in vitro studies have converged on a small cluster of conserved, positively charged or aliphatic residues of L7/L12, which may interact with the G protein factors EF-Tu, EF-G, RF3, and IF2 (9,10,30).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments on miscoding show that the protein with the inserted fourteen residues (pPRI2, Table 1) has a lower level of miscoding. The partial deletion of the flexible region of the LT/LI2 also affects the miscoding level [9,10,20].…”
Section: I011mentioning
confidence: 99%
“…Expression of the L12 w.t. gene without induction (1) and after induction by IPTO (2); expression of LI2-pPRI 1 (3), LI 2-pPR12 (4), LI2-pPR28 (5), LI2-pPK37 (6) and LI2-pPR38 (7); markers (Pharmacia) 14, 20, 30, 43, 67, and 94 kDa (8,9); purified proteins LI2-pPRI2 (10) and LI2-pPR38 ill).…”
Section: I011mentioning
confidence: 99%
See 2 more Smart Citations